Coal and Mines in the Era of Fascist Ventennio in Italy - Roberta Varriale; Silvana Bartoletto; Sabrina Sabiu (Histories)
Access to raw materials has always been one of the main drivers of economic growth. In Italy, where the relationship between exports and imports has always been negative, during the fascist period, several new opportunities and limits were introduced and many efforts were made to promote the exploitation of Italian resources to support the energy transition, focusing on energy autonomy. But were these efforts sufficient to ensure the achievement of the objectives, or did the internal demand for coal always make trade and technological exchanges with foreign countries necessary, despite what fascist propaganda showed through its communication strategy during the so-called Ventennio? This research, which is part of a significant debate regarding the role of mines in the economic, social, and cultural development in Italy during fascism, was based on the analysis of several series of unpublished data regarding energy consumption, imports, and production in Italy and the international technological debate about Sardinia Island, where the most productive Italian coal mines were opened. Based on a comparison of results, this research aimed at refuting the hypothesis that during the energy transition from wood to coal, Italy was closed both to the international technical, scientific, and methodological debates regarding the mining sector and energy imports.